A Short Introduction Concerning the Implementation of the Horizon System at the Nicholas Copernicus University Library in Toruñ - Poplawska, Lucyna (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
I would like to present an outline of the Horizon system, its history, environment, and state of implementation at the Nicholas Copernicus University Library in Toruñ at the moment, and the situation in the Map Department. Horizon is a third generation system (i.e. one of the latest of several library management systems) marketed by Ameritech Library Services, a subsidiary of the Ameritech Corporation, one of the world’s largest communication companies. The new system Horizon was built on the Marquis, Dynix library system, and is being developed by Ameritech Library Service in collaboration with the University of Chicago and Indiana University. It was first introduced in the USA in 1991. By August 1998, Horizon had been installed in about 570 libraries, located in the USA, Canada, Mexico, South America, Australia, New Zealand, Thailand, China, Saudi Arabia and many European countries. The first library in Europe to use this system was Technische Fachhochschule in Berlin.